2004
DOI: 10.1016/s0006-3495(04)74096-5
|View full text |Cite
|
Sign up to set email alerts
|

The Binding of κ-Conotoxin PVIIA and Fast C-Type Inactivation of Shaker K+ Channels are Mutually Exclusive

Abstract: Kappa-conotoxin PVIIA (kappa-PVIIA), a 27-amino acid peptide identified from the venom of Conus purpurascens, inhibits the Shaker K+ channel by blocking its outer pore. The toxin appears as a gating modifier because its binding affinity decreases with relatively fast kinetics upon channel opening, but there is no indication that it interferes with the gating transitions of the wild-type channels (WT), including the structural changes of the outer pore that underlie its slow C-type inactivation. In this report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…Our study provides a structural model for the chemical shift changes observed upon high-affinity binding of KTX to the chimeric potassium channel KcsA-Kv1.3. Due to their sharing of many important features, such as dependence on the same set of point mutations in the external pore vestibule, or sensitivity to external tetraethylammonium (TEA), a connection between the association of peptidic toxins and C-type inactivation was long assumed, but could not yet be clearly established by using low-affinity toxin peptides (Kurata and Fedida, 2006;Oliva et al, 2005;Koch et al, 2004). These conformational effects could thus far only be studied indirectly because of the lack of a high-resolution structural picture for both toxin binding and C-type inactivation (Kurata and Fedida, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides a structural model for the chemical shift changes observed upon high-affinity binding of KTX to the chimeric potassium channel KcsA-Kv1.3. Due to their sharing of many important features, such as dependence on the same set of point mutations in the external pore vestibule, or sensitivity to external tetraethylammonium (TEA), a connection between the association of peptidic toxins and C-type inactivation was long assumed, but could not yet be clearly established by using low-affinity toxin peptides (Kurata and Fedida, 2006;Oliva et al, 2005;Koch et al, 2004). These conformational effects could thus far only be studied indirectly because of the lack of a high-resolution structural picture for both toxin binding and C-type inactivation (Kurata and Fedida, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…To examine the validity of this prediction, we have sought an experimental design that would allow us to separate between the two steps of Cs1 action, namely toxin binding and pore-collapse. To this end, we have employed the Shaker KD M448K mutant, which exhibit accelerated slow inactivation, while retaining high affinity for toxins ( Fig S6A; Koch et al, 2004). While Cs1 binding to unmodified Shaker KD was voltage-insensitive ( Fig.…”
Section: Channel Block By Conkunitzin-s1 Is Slowed By Heavy Watermentioning
confidence: 99%
“…Interestingly, a bidirectional modulation of ion channels is brought about by a number of conditions, such as changes in the holding potential (Kass, 1987). It is also not restricted to low molecular weight compounds (Koch et al, 2004;Mezler et al, 2012a) and may simply be observed by changing the expression system (Mezler et al, 2012a). Cho and Meriney (2006) reported a 427% attenuation of the deactivation kinetics of calcium currents by roscovitine in Xenopus motorneurons and consequently increased transmitter release.…”
Section: Low Molecular Weight Calcium Channel Blockersmentioning
confidence: 99%